The velvet claw - Jacobi, Derek; Barker, Melinda (London : BBC Enterprises, 1993)
With 236 species contained in 8 families and over million years of evolution, the variety and adaptability of carnivores is breathtaking. This stunning video from the major BBC TV series traces the amazing story of their evolution
Executive producer, Mike Beynon
Narrated by Derek Jacobi
Keywords: Carnivora